Freshwater cultured pearls from Kentucky Lake - Table S2 - Gabriela Farfan; Chunhui Zhou; Ian Orland; John W Valley (PANGAEA, 2021)
This Dataset serves as supplementary table S2 for our publication (Farfan et al, 2021). It contains all of the mineralogical, oxygen isotope, and Kentucky Lake environmental data compiled for the study, set into nacre-transect space defined by the SIMS-pits taken during oxygen isotope analyses.
In: Farfan, G et al. (2021): Mineralogical and isotopic data of freshwater cultured pearls from Kentucky Lake with associated lake environmental data [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.938370